The motivation of profits and the self concept in students of the greater national University of San Marcos - Vicuña Peri, Luis (2004)
OBJECTIVE: To identify the relation between autoconcepto with the types of motivation proposed by Mc Clelland: to be able, affiliation and profit. Also to find out the paper that fulfHls the academic yield and sex on the selfsteem. To identify the paper that fulfills the academic yield and sex on the components of the motivation: affiliation, power and I obtain. DESIGN: The present investigation is corelational and descriptive. MATERIAL And METHODS: Working with a sample of 768 students, with academic specialties of areas To, B and C. To them it was psychometrically applied to the questionnaire of self concept of Jose Navas and the elaborated and reviewed inventory to them of Motivation for this study. RESULTS: The analysis of results was carried out in 3 steps. First by means of the correlation of self concept with each one of the components of the motivation and these to each other. The second step was by means of the contrast of autoconcepto and the motivation of affiliation or profit in function to the academic area and sexo Finally, one became a description of the sample examined on the basis of the obtained averages and percentage distribution by categories. CONCLUSIONS: One concludes that self concept with the motivation of connection, power and profit is variable independent. The components of the motivation correlate significantly on them, which indicates that they are component of a same factor. On the other hand, self concept tends to be influenced by sex, and not thus by the academic area of origin However, the affiliation motivation more is affected by the academic area that by sex; and as much in the motivation of being able and profit the sex or the area of academic property they influence significantly. By the descriptive results we found that more of 60% of the examined sample it is located in the categories of high tendency, which is a good indicator with respect to the form as they are described themselves, like also in the reason that can maintain to them constant in the search of the success.